The Influence Of Good Corporate Governance (Gcg), Environmental, Social, And Governance (Esg), And Intellectual Capital On The Value Of Banking Companies In Indonesia For The Period 2020-2024 - Vivi Riskianti; Muslimin Muslimin; Cici Rianty K.Bidin; Anisah Anisah (UNIVED Press, 2026)
This study aims to analyze the effect of Good Corporate Governance (GCG), Environmental, Social, and Governance (ESG), and Intellectual Capital (IC) on the value of banking companies in Indonesia for the period 2020–2024. This study uses an explanatory quantitative approach with 20 banks selected through purposive sampling, resulting in 100 data observations. The GCG variable is proxied by institutional ownership, independent commissioners, and audit committees, ESG is measured using the ESG Disclosure Index, IC is measured using the Value Added Intellectual Coefficient (VAIC), and company value is proxied by Tobin's Q. Data analysis was performed using SEM-PLS through SmartPLS software. The results of the study indicate that Good Corporate Governance (GCG) does not have a significant effect on company value, while Environmental, Social, and Governance (ESG), and Intellectual Capital (IC) have a positive and significant effect on company value.